8 - African Association of Political Science Resolution on Walter Rodney 26 May 1981. - HEINECKE, H. (Africa Development, 1981)
We, the members of the African Association of Political Science, here assembled in Harare, Zimbabwe, May 1981 : - Recognizing the importance of the commitment of African scho- lars to the struggles of the peoples of Africa against colonialism, imperia- lism and neo-colonialism; do hereby Deplore arbitrary acts of governments to silence the right of African scholars and scholars of African descent to freely express their views on the condition of the African peoples, and condemn in the stron- gest terms acts of arbitrary imprisonment and acts of assasination against committed scholars like Walter RODNEY of Guiana who was a son of both the African and the West Indian soil, and who made a significant contribu- tion to the development of the struggles of the peoples of Africa and of all oppressed peoples everywhere; And Associate ourselves with the demand for an international inquiry into the death of Walter RODNEY. A A P S